Made Yum (MY) Enterprise / Nuraina Athiqah Mohammad - Mohammad, Nuraina Athiqah (2020)
Made Yum (MY) Enterprise is a start-up bread bakery retail establishment located in Shah Alam. Made Yum (MY) expects to catch the interest of a regular loyal customer base with its broad variety of bread products. The company plans to build a strong market position in the town, due to the mild competitive climate in the area. Made Yum aims to offer its products at a competitive price to meet the demand of the middle-to higher-income local market area residents and tourists. Made Yum (MY) is incorporated in the state of Selangor, Malaysia. It is sole proprietorship which equally owned and managed by a general manager, Nuraina Athiqah Mohammad which has extensive experience in sales, online marketing. The company intends to hire three chefs and two chef assistant in full-time bread bakers and one cashier to handle customer service and day to day operations. This company also offers wide range and variety of breads which freshly bakes from oven. Top three from them are Chocolate bread, Butterscotch and croissants. All are made from good and high quality materials to keep the breads quality. Six to eight moderate batches of bakery and pastry products are prepared during the day to assure fresh baked goods are always available.